KOMPETENSI GURU ATASI KESULITAN BELAJAR MATEMATIKA SISWA KELAS IV PASCA COVID-19 - Sumiati Sumiati; Parni Parni; Hadisa Putri (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
This study uses a qualitative approach and the type of research used is descriptive. The data collection techniques used are interviews, observation, and documentation. Then the data analysis techniques used in this study are data reduction, data display/data presentation, and drawing conclusions. While the technique of checking the validity of the data researchers use triangulation techniques and member checks. The results of this study indicate that: 1) Students' learning difficulties can be concluded that the difficulties experienced by students with learning difficulties include: a) Difficulty in Understanding Symbols; b) Difficulty in Understanding Concepts; c) Difficulty in Calculation; d) Difficulty in Understanding Principles; 2) Simply put, the implementation of teacher competencies as educators is: a) Ensuring Student Readiness in Learning Mathematics; b) Use of Mathematics Learning Media; c) Solving Problems According to Student Abilities; d) Teacher Assessment of Learning; 3) The main inhibiting factor is still many obstacles, because students are considered as the covid-19 generation, so there are still many students who are not actually ready to be in grade IV. Supporting factors include communicative and trainable teachers who master teacher competencies and learning theories, mathematics learning principles, and the necessary teaching methods.